2017
DOI: 10.1016/j.ultsonch.2016.12.032
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonic assisted synthesis of Bikitaite zeolite: A potential material for hydrogen storage application

Abstract: Li containing Bikitaite zeolite has been synthesized by an ultrasound-assisted method and used as a potential material for hydrogen storage application. The Sonication energy was varied from 150W to 250W and irradiation time from 3h to 6h. The Bikitaite nanoparticles were characterized by X-ray diffraction (XRD), infrared (IR) spectral analysis, and field-emission scanning electron microscopy (FESEM) thermo-gravimetrical analysis and differential thermal analysis (TGA, DTA). XRD and IR results showed that phas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 36 publications
0
24
0
Order By: Relevance
“…Although from Table , it is seen that P5 powder has lower pore wall thickness, the rupturing of mesopore structure upon the application of high sonication energy makes it a very low surface area powder. Figure shows the comparison of H 2 adsorption capacity of SBA‐15 powders synthesized in this work with other reported values of hydrogen adsorption by other different materials . It is clear that the present result of hydrogen adsorption capacity of the high surface area powder P4 is higher than the reported value till date.…”
Section: Resultsmentioning
confidence: 54%
“…Although from Table , it is seen that P5 powder has lower pore wall thickness, the rupturing of mesopore structure upon the application of high sonication energy makes it a very low surface area powder. Figure shows the comparison of H 2 adsorption capacity of SBA‐15 powders synthesized in this work with other reported values of hydrogen adsorption by other different materials . It is clear that the present result of hydrogen adsorption capacity of the high surface area powder P4 is higher than the reported value till date.…”
Section: Resultsmentioning
confidence: 54%
“…10.43–18.29% loss up to 200 °C may be attributed to the desorption of physically adsorbed water 34 . With further heating up from 200–500 °C, the weight loss of the synthesized samples of about 0.19–2.42% weight loss are due to the decomposition and removal of hydroxyl group in the as-synthesized zeolite samples 39 . The weight loss of the synthesized samples in current study are comparable with the work reported by Liu et al .…”
Section: Resultsmentioning
confidence: 99%
“…In the case of Bikitaite zeolite, the molar composition of the sol used for the synthesis was 10 Li 2 O:0.5 Al 2 O 3 :2.5 SiO 2 :600 H 2 O [56]. Like the previous protocol, two reactant mixtures were prepared respectively by suspending the measured amount of colloidal silica and lithium hydroxide in deionized water (DI water) in a glass beaker (mixture 1).…”
Section: Methodsmentioning
confidence: 99%
“…This method has potential advantages in terms of achieved preferential orientation control of membrane microstructure and higher reproducibility if compared with the in situ synthesis method [39]. Extensive studies have been performed aiming at investigating potential of zeolites and derived membranes for gas separation [40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56]. Specific zeolites have a high capacity and selectivity for the gases of interest, leading to compact and efficient separation/storage systems.…”
Section: Introductionmentioning
confidence: 99%